Possible icelandic tephra found in european colle gnifetti glacier - Luongo, Matthew; Bohleber, Pascal (Geochemistry, geophysics, geosystems, 2017)
Volcanic ash (tephra) provides unique time markers (isochrons) that are often used as an independent age-control tool for stratigraphic correlations of paleoclimate archives from ice cores. However, little credence has been given to the notion of finding tephra in ice cores collected in the European Alps because of the relatively large distance from volcanic sources and the presumed nature of regional atmospheric circulation patterns. We filtered particles from melted ice core drilling chips gathered roughly every meter during a 2013 drilling operation at Colle Gnifetti glacier in the Swiss-Italian Alps (45°55.74′N, 7°52.58′E, 4450 m asl). One filter, preliminarily dated to the nineteenth century by annual layer counting, contained a group of six visually similar tephra particles. Analyzing their chemistry using a scanning electron microscope equipped with an energy-dispersive x-ray spectrometer established that the six particles were volcanic in origin and are very similar in composition (a distinctive geochemical signature), pointing to a single volcanic eruption source. We proposed that one of several massive nineteenth century Eastern Icelandic eruptions is a potential source given eruption timing, size, tephra dispersion area, and similarities in chemical composition. This first finding of tephra in an Alpine ice core contributes to a regional tephrochronological framework that can be adapted for future correlation among different paleoclimate sequences.
Published online 13 NOV 2017
Gesehen am 28.06.2018